PROSOPIS CINERARIA LEAF EXTRACT PROTECT H2O2 INDUCED OXIDATIVE STRESS-INDUCED CELL DEATH IN SACCHAROMYCES CEREVISIAE - Bangaruswamy, Dharani; Jambunathan, Sivaprabha; Padma, Palghat Raghunathan; Sundaravadivelu, Sumathi (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Saccharomyces cerevisiae cells exposed to oxidant damage were used as in vitro model to assess the cytotoxic effect and apoptotic events in the presence and absence of the methanolic leaf extract of Prosopis cineraria. Methods: The cytotoxicity assays methyl - tetrazolium, sulforhodamine B (SRB) and lactate dehydrogenase and apoptosis related changes namely, morphological and nuclear changes by various staining techniques (Giemsa, propidium iodide [PI], ethidium bromide [EtBr] and 4',6-diamidino‑2-phenylindole), and DNA damage (diphenylamine method) were assessed in S. cerevisiae cells with/without leaf extract and oxidant (hydrogen peroxide). Results: The results of the cytotoxicity assays and apoptotic study showed that H2O2 exposure in S. cerevisiae cells significantly decreased the viability of the cells. In leaf extract alone treated group, there was no significant reduction in the viability of the cells. When the leaf extract was co-treated with oxidant, there was an increase in the percent viability of the cells indicating that the extract was capable of protecting the cells from oxidative stress. Conclusion: The apoptosis-inducing effect of the oxidant was effectively counteracted by the presence of methanolic extract of P. cineraria leaves. Keywords: Saccharomyces cerevisiae, Oxidative stress, Cytotoxicity, DNA damage.